Pengaruh Penggunaan Sosial Media, Influencer dan Konten Visual Terhadap Keputusan Pembelian Skincare Kahf di Tiktok - Vieri, Christian; Sarah, Siti (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study explores the influence of social media, influencers, and visual content on purchasing decisions for "Kahf" skincare products on TikTok. The way people communicate, exchange knowledge, and shop has evolved in the modern digital era due to advances in information and communication technology. This study highlights the importance of social media in influencing consumer behavior, primarily through the TikTok platform which has a wide and diverse user base. A pre-survey was conducted on 30 respondents to measure the engagement and impact of TikTok visual content and influencers on purchasing decisions. The results show that although the "Kahf" product has used social media as a means of promotion, the level of purchasing decisions is still low. We anticipate that this study will be a foundation for future research on marketing skincare products through social media and provide substantial theoretical and practical contributions to digital marketing and consumer behavior